Characteristic of the plant communities of the Ikonnikovia kaufmanniana population at the Syugaty low-mountain (Experimental biology, 2016)
Full geobotanical characteristic and floristic analysis of plant communities of the Ikonnikovia kaufmanniana population in the southwestern part of the mountain Syugaty are given in article. The authors note that Ikonnikovia kaufmanniana is really a rare and endemic plants with shrinking natural habitat. Its population in the mountains Syugaty occupies a limited area and never form a continuous cover, and meets separate spots, mostly in the northern, north-western and north-eastern exposure of the slope. The territory of mountains Syugaty are heavily used all summer as pasture by individual farmers of Enbekshikazakh and Uighur districts of Almaty region. Because of that there is a serious threat of its populations. In this connection, it is need to declare a protected zone or, at least, it is necessary to regulate grazing, especially flocks of sheep at Syugaty low mountain, where natural Ikonnikovia kaufmanniana population are meet.
Keywords: population; association; endemic; ephemera; ephemeroid.